ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN KOPERASI SAKINAH - Abdan Syakura (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One of the easiest to read benchmarks of organizational growth that can be considered good is the performance of financial statements based on increased profits. This can be illustrated in the financial performance report for a certain period. In order for financial statements to be meaningful for internal parties and cooperative members, it is necessary to analyze the relationship of the items in the financial statements which is often called financial statement analysis. The purpose of this study was to determine how the financial performance of the Sakinah Cooperative in terms of financial ratio analysis. The data analysis method used is descriptive quantitative method using the measurement of liquidity ratios, solvency and profitability from the annual report issued by the Sakinah Cooperative. Based on the overall liquidity ratio, Sakinah Cooperative is in good condition, during the period from 2020-2021. Based on the solvability ratio, the Sakinah Cooperative is in a solvable position, because the Sakinah Cooperative's capital is sufficient to cover the debts given by creditors. Based on the overall profitability ratio, Sakinah Cooperative is in a good position despite a decline in the profitability ratio in 2021